Secondary Metabolite Profiling, Anti-Inflammatory and Hepatoprotective Activity of Neptunia triquetra (Vahl) Benth - Nasir Aziz Wagay; Shah Rafiq; Mohammad Aslam Rather; Younas Rasheed Tantray; Feng Lin; Shabir Hussain Wani; Ahmed M. El-Sabrout; Hosam O. Elansary; Eman A. Mahmoud (Molecules, 2021)
The present study aimed to analyze the phytoconstituents of Neptunia triquetra (Vahl) Benth. Anti-inflammatory and hepatoprotective activities of ethanol (EE), chloroform (CE) and dichloromethane (DCME) of stem extracts were evaluated using in vivo experimental models. The extracts were analyzed for phytoconstituents using GC-HRMS. Anti-inflammatory activity of CE, EE and DCME was accessed using carrageenan-induced paw oedema, cotton pellet-induced granuloma and the carrageenan-induced air-pouch model in Wistar albino rats. The hepatotoxicity-induced animal models were investigated for the biochemical markers in serum (AST, ALT, ALP, GGT, total lipids and total protein) and liver (total protein, total lipids, GSH and wet liver weight). In the in vivo study, animals were divided into different groups (six in each group) for accessing the anti-inflammatory and hepatoprotective activity, respectively. GC-HRMS analysis revealed the presence of 102 compounds, among which 24 were active secondary metabolites. In vivo anti-inflammatory activity of stem extracts was found in the order: indomethacin > chloroform extract (CE) > dichloromethane extract (DCME) > ethanolic extract (EE), and hepatoprotective activity of stem extracts in the order: CE > silymarin > EE > DCME. The results indicate that N. triquetra stem has a higher hepatoprotective effect than silymarin, however the anti-inflammatory response was in accordance with or lower than indomethacin.